After definitions: Genre, categories, and cognitive science - Sinding, Michael (Genre, 2002)
Keywords: genre theory; cognitive science; categorization; novel; menippean satire; film noir

"Against Opposition" - Sinding, Michael (2002)

“‘A Sermon in the Midst of a Smutty Tale’: Blending in Genres of Speech, Writing and Literature.” - Sinding, Michael (Cognitive Literary Studies: Current Themes and New Directions, 2012)
Genre mixture is central to genre theory, in both literary and discourse studies. I characterize genres as multidimensional schemas integrating frames for action, situation, and discourse. Blending theory, as a model of the interaction of schemas, can clarify genre mixture and help to connect these fields. Laurence Sterne’s Tristram Shandy exemplifies Bakhtin’s view of the early novel cannibalizing extraliterary genres. Sterne framed his famous “Abuses of Conscience” sermon in four genre contexts: first, as the annual assize sermon at York Minster (1750); second, as a six-penny pamphlet (1750); third, integrated into Tristram Shandy (1760); fourth, in a collection of his sermons (1760). These productions vary considerably in purpose, rhetorical situation, and audience response. Notably, Tristram and Sterne’s sermons were great but mixed successes. The clash of the pious genre in the profane story, and Sterne’s attribution of his sermons to his comic alter-ego Mr. Yorick, prompted both denunciation and praise. I compare the blending and framing involved in the novel with the other cases, to examine how different conceptual networks produce different categorizations, meanings, and responses. I reflect on principles of genre blending relating the sermon to the book as a whole.
Keywords: Sterne; genre mixture; conceptual blending; sermon; novel

Assembling spaces: The conceptual structure of allegory - Sinding, Michael (Style, 2002)
Blending theory accommodates more complex mappings that the source-target projections of the Lakoff-Johnson theory of metaphor. It can resolve a number of traditional puzzles about allegory, while preserving critical insights and supporting them with a sophisticated linguistics. I examine Prudentius's Psychomachia to show how prototypical allegories use organizing metaphors but exhibit blending operations. I suggest that from a latent existence in language, allegory arises as an imagined scene, then expands to narratives. This can illuminate how blends get elaborated. I explore the nature of variant forms of allegory in blending terms, looking closely at Kafka's Trial.
Keywords: allegory; conceptual blending; Prudentius; Kafka

“A Triple-Frame Model of Genre: Framing for Discourse Sequencing.” - Sinding, Michael (Genre in Language, Discourse and Cognition, 2016)
I propose a theoretical model of genre with parameters organized in terms of the concept of “frame.” The model has three nested frames: a sociocognitive action frame contains a rhetorical situation frame, which contains a discourse structure frame. I motivate the model in relation to existing research on both literary and extraliterary genres, sketch its advantages and the lines of research it suggests, then address challenges to it. First, to clarify how genre relates to language, discourse and cognition, and my investments in various research areas, I review major conundrums about genre identity. Second, I argue for an inclusive approach to genres, as against defining “genre” to suit assumptions and methods. Third, I discuss the broader conception of discourse structure and sequencing that this inclusive approach entails. Fourth, I investigate frame-based sequencing in text composition—specifically, how poets adapt everyday genre frames for literary purposes. I propose a theoretical model of genre with parameters organized in terms of the concept of “frame.” The model has three nested frames: a sociocognitive action frame contains a rhetorical situation frame, which contains a discourse structure frame. I motivate the model in relation to existing research on both literary and extraliterary genres, sketch its advantages and the lines of research it suggests, then address challenges to it. First, to clarify how genre relates to language, discourse and cognition, and my investments in various research areas, I review major conundrums about genre identity. Second, I argue for an inclusive approach to genres, as against defining “genre” to suit assumptions and methods. Third, I discuss the broader conception of discourse structure and sequencing that this inclusive approach entails. Fourth, I investigate frame-based sequencing in text composition—specifically, how poets adapt everyday genre frames for literary purposes.
Keywords: genre; cognition; frame; sociocognitive action; rhetorical situation; discourse structure

Beyond essence (or, getting over 'there'): Cognitive and dialetical theories of genre - Sinding, Michael (Semiotica, 2004)
Keywords: genre; cognitive model; ideology

“Blending in a baciyelmo: Don Quixote’s Genre Blending and the Invention of the Novel.” - Sinding, Michael (Blending and the Study of Narrative., 2012)
An account of Cervantes’ "invention of the novel"–by mixing the genres of chivalric romance and picaresque tale–in terms of Blending Theory has several related aims, concerning issues in several related areas. First, regarding this text and its genre, I want to clarify Don Quixote’s structure, and its decisive impact on the novel genre. I will describe how Cervantes created a new genre template that later writers adopted by blending two known genres. Second, regarding literary genre theory, I want to clarify how genre blending shapes and refracts through various textual levels. I suggest that the narrative level of genre structure, the level of typical characters and actions, is the most fundamental one, as it has more influence on the structure of other levels than they have on it. This level is also fundamental in the unfolding of genre blends. Third, I hope this case study will also clarify the benefits and challenges of using Blending Theory to model cognitive structures and processes subtending discourse. Literary genre blending highlights the potential variability, complexity, and depth of ‘full meaning construction’ in discourse, and the case of Don Quixote suggests that it may be unrealistic to expect a simple answer to the question of exactly whose mental processes are being modeled in blending analyses. Finally, genre blending analyses offer a vantage on the cognitive study of culture, because they can clarify the structure and history of the worldviews that are combined and transformed in genre mixtures such as Cervantes’.
Keywords: Genre mixture; conceptual blending; Don Quixote; chivalric romance; picaresque; narrative structure

Body of Vision: Northrop Frye and the Poetics of Mind - Sinding, Michael (University of Toronto Press, 2014)
In Body of Vision, Michael Sinding connects Northrop Frye’s groundbreaking contributions to our understanding of the human imagination with cognitive poetics – the cutting-edge school of literary criticism that applies the principles of cognitive science to the interpretation of literary texts and contexts. Sinding undertakes this task through analyses of the interplay of metaphoric and narrative schemas in several forms of cultural mythology. Sinding identifies the profound connections between cognitive views of language, literature, and culture and Frye’s views by exploring three related aspects of Frye’s work – meaning and thought, culture and society, and literary history. He investigates these connections through detailed studies of major cultural texts including Dante’s Divine Comedy, Hobbes’ Leviathan, Rousseau’s Social Contract, and Milton’s "Lycidas." By linking Frye’s classic studies to exciting recent approaches in the humanities and the cognitive revolution of the past few decades, Body of Vision casts Frye’s achievements in a fascinating new light.
Keywords: Northrop Frye; cognitive poetics; literature; culture; metaphor; narrative; genre

Cognitive poetics in practice - Sinding, Michael (Cognitive Linguistics, 2007)

"Foregrounding" - Sinding, Michael (2004)

Framing Monsters: Multiple and Mixed Genres, Cognitive Category Theory, and Gravity's Rainbow - Sinding, Michael (Poetics Today, 2010)
This article argues for a cognitive view of genre. Specifically, a cognitive view of categorization helps clarify how texts can participate in multiple genres-by instantiating several different genres more or less equally well and by mixing several genres. I respond to certain recurring assumptions in recent work on genre about the nature of categories and categorization, elaborating on John Frow's incisive critique of misconceptions of genre but correcting his discussion of cognitive poetics. I draw on concept and category research to sketch the three main contemporary approaches to categorization via prototype, exemplar, and knowledge theories. Against this background, I review the many genres that have been attributed to Gravity's Rainbow, then examine three influential generic framings of this text and what the text can tell us about the nature of categories and how people use them. I conclude by discussing the ways this example is particularly revealing about how prototypes, exemplars, and knowledge interact, how experts use categories to understand and experience the very rich and complex realities of their domains of expertise, and how this new understanding of categorization can help clarify Thomas Pynchon's blending of genres.
Keywords: genre; cognitive science; categorization; conceptual blending; Thomas Pynchon criticism

From fact to fiction: The question of genre in autobiography and early first-person novels - Sinding, Michael (Sub-Stance, 2010)
Keywords: genre; categories; prototype theory; autobiography; novel

“From Words to Worldview: Reframing Narrative Genres in the French Revolution Debate.” - Sinding, Michael (Poetics Today, 2017)
Special issue on Situated Cognition and the Study of Culture This article draws together overlapping cognitive analyses of political thought, emotion and language, and shows how they can be supplemented with literary analyses of genre to illuminate the workings of the French Revolution Debate of 1790s Britain. It focuses on enriching George Lakoff’s theory of the multiple levels of framing in discourse, concentrating on the interplay of argument and narrative frames. Studies of emotion and mood in narrative genres are adapted to refine Lakoff’s account of narrative, making it more complex, systematic, and sensitive to historical context. Applying the revised theory, the essay characterizes contrasts between Edmund Burke’s and Thomas Paine’s thought at all levels of framing. It shows how their lexical frames for “Revolution” diverge as their main arguments craft opposing issue-defining frames for the central moral issue of Revolution-vs.-reform. Those arguments highlight different key figures and events, yet draw on similar narrative genres to frame them. Importantly, high genres of heroic romance inspire elevation towards one’s own side by celebrating victories and lamenting tragedies, and low genres of satire inspire contempt towards opponents by ridiculing deserved failures and absurd successes. Thus narrative genre ties surface-frame phrases like “rights of man” and “swinish multitude” to deep-frame assumptions about more fundamental concepts (human nature, society, government).
Keywords: framing; emotion; genre; politics; French Revolution Debate

“From World to Worldview: An Energy Principle of Psychosocial Dynamics.” - Sinding, Michael (The Cognitive Humanities: Embodied Mind in Literature and Culture, 2016)
To explain how cultural worldviews cohere, we need to develop principles of worldview structure. Image schemas and force dynamics must be central to worldview structure, since they are central conceptual structures of both metaphor and narrative, and both metaphor and narrative are central organising structures of worldview. However, the role of these conceptual structures in discourse has not been adequately studied, and they need to be developed (scaled up, supplemented and integrated) in order to represent rich and extended narrative and metaphoric thought adequately. A promising line of development is to link these structures with ‘intuitive ontology’ (especially ‘naïve physics’)—specifically, to characterise energy as a principle of conceptual structure for models of the physical world that can be used in metaphor and narrative to model the psychosocial world. I begin by considering William Blake’s Marriage of Heaven and Hell (1790) as a precursor vision of embodied cognition, as Blake declares that there is no soul distinct from body; and energy, which is life and delight, is from the body. I then examine visual and linguistic narrative representations of energy patterns, in popular culture examples, in Blake’s illustrations of good and wicked souls for Robert Blair’s poem The Grave (1805), and in a key scene in William Godwin’s novel Caleb Williams (1794). Turning to political argument and worldview, I show how Edmund Burke and Thomas Paine frame the French Revolution under contrasting models of psychosocial structures, causality and valuation. The metaphor scenarios (see Andreas Musolff, 'Metaphor Scenarios in Public Discourse', Metaphor & Symbol 21, 1 (2006), 23–38) in their arguments are of various ontologies and levels of schematicity: substances (property, body, parts, ties, mass), forces (tie, impulse), forceful movements (receive, hold, transmit, bind, circulate, pass-through, invigorate, dissolve, bring-together). Yet these arguments integrate the scenarios into broader psychosocial stories that are coherent and easily understood. Thus I propose a method for coordinating metaphor analysis at several levels of discourse: metaphor scenarios, metaphoric schema-structures, and super-schematic metaphoric narratives. Using this method, I characterise Burke’s and Paine’s central analogies for sociopolitical order; their moral priorities; and their moral blind spots. Throughout, I argue that it is only at the level of energy structure that we can specify how sequences of scenarios get integrated into patterns; and how coherent but opposite patterns of psychosocial energy underpin political models.
Keywords: metaphor; narrative; image schema; intuitive ontology; worldview

Genera mixta: Conceptual blending and mixed genres in "Ulysses" - Sinding, Michael (New Literary History, 2005)
This essay draws on cognitive science and cognitive linguistics to illuminate what may be the most important issue in genre theory at present: genre mixture and hybridization. Genres have been very productively treated as cognitive schemas, but so far such treatments have not adequately accounted for critics' descriptions of their encounters with complex works, because they have lacked a model of how schemas are modified, rearranged, and combined. In the past decade, however, Gilles Fauconnier and Mark Turner have worked out just such a model in considerable detail. Conceptual Blending Theory has roots in linguistics, psychology, literary hermeneutics, and brain science. Fauconnier and Turner and others have used Blending Theory to analyze a wide range of thought and meaning, both m undane and highly creative, in the arts, sciences, and everyday life. Taking the example of Joyce's Ulysses, and focusing on the "Circe" episode, I discuss various kinds of genre mixture, showing how surface details as well as structural aspects of the text can be explained in terms of the processes and principles of conceptual blending.
Keywords: genre mixture; schema; conceptual blending; Joyce

Governing spirits: Body politic scenarios and schemas in the French Revolution debate - Sinding, Michael (Warring with Words: Narrative and Metaphor in Politics, 2015)
Keywords: narrative; metaphor; body politic; French Revolution debate

Inwit of inwit - Sinding, Michael (Style, 2004)
David Lodge's latest books, Thinks... and Consciousness and the Novel, form a pair: a novel and an essay collection both confronting the budding scientific field of "consciousness studies," exploring its challenging implications for traditional humanistic concerns. Lodge observes that literature, especially the novel, is often seen as providing the fullest representation and analysis of consciousness. He examines how novelists developed techniques for this purpose, and how their conceptions of human experience and self have evolved. Consciousness studies parallels poststructuralism in its frequent antagonism to traditional humanistic values, but Lodge sees scientific and humanistic knowledge as complementary, not contradictory. I suggest that, rather than complement, they might more fully cooperate. I sketch some ways to develop Lodge's ideas about literature as contributions to the study of consciousness, using his books as examples.
Keywords: consciousness; the novel; metaphor; David Lodge

Lapsed latin: Etymology, image schemas, and multilingual wordplay in Stevens' "Notes Toward a Supreme Fiction" - Sinding, Michael (Wallace Stevens Journal, 2008)
Keywords: wordplay; etymology; metaphor; image schema

“Letterier: Categories, Genres, and Epistolarity.” - Sinding, Michael (What is a Letter? Essays on epistolary theory and culture, 2017)
This essay approaches the question ‘What is a letter?’ via two more general questions, ‘What is a genre?’, and ‘What is a category?’ It offers an overview of how concept and category research can help answer these questions; how scholarship on letters might extend category research; and how this cross-fertilization may illuminate epistolary texts, structures, cultures and histories.
Keywords: genre; categories; concepts; letters; epistolarity

"Metaphor in the raw" - Sinding, Michael (2000)

“Mythology on the Move: Narrative Archetypes in Framing and Worldview.” - Sinding, Michael (2015)
Keywords: Northrop Frye; framing; narrative; archetype; worldview

Narrative and Cognition in Literature and Science - Sinding, Michael; Heydenreich, Aura; Mecke, Klaus (De Gruyter Brill, 2025)

Reframing Frye: Bridging culture and cognition - Sinding, Michael (Northrop Frye: New Directions from Old, 2009)

Seeing double: Shared identities in physics, philosophy and literature - Sinding, Michael (2004)

Social Minds and Metaphor in Rousseau - Sinding, Michael (Narrative, 2015)
Rousseau’s writings seem to call out for analysis in terms of social minds, because he looms so large in the conceptual framing of modern psychosocial dynamics in their primary units, and the narrative framing of them in their primary cultural genres. He did much to invent our ideas of the solitary individual in autobiography, friends and lovers in the sentimental novel, and democratic societies in political philosophy. If narratology needs to address the “formation, development, maintenance, modification, and breakdown of . . . intermental systems” (Palmer 41), and metaphor is among our central instruments for conceptualizing and expressing such subjective and abstract matters, then narratology should get metaphorical. Underlying Rousseau’s revolutionary writings on social minds are multiple models of intermentality, built partly from particular combinations of metaphors. To understand how intermentality is narrated, we need to understand how metaphors are narrated. I develop this perspective by comparing the role of metaphor in framing kinds of social minds in Rousseau's novel Julie (1761) and his treatise The Social Contract (1762).
Keywords: social minds; metaphor; fictional narrative; factual narrative; Rousseau

Storyworld Metaphors in Swift’s Satire - Sinding, Michael (Beyond Cognitive Metaphor Theory: Perspectives on Literary Metaphor, 2011)
In this innovative collection, an international group of scholars come together to discuss literary metaphors and cognitive metaphor theory. The volume's goals are three-fold. The first aim of the book is to present some recent approaches to metaphor which have no immediate connection with cognitive metaphor theory and have developed independently of it. While the cognitive approach has become the leading paradigm in the English speaking world, elsewhere (in Europe) rhetorical, semantic, and logical models have remained in use and continue to be elaborated. These models have so far had little international exposure. Their inclusion in this study is meant to provide a balance to the cognitive paradigm and to open up a possible discussion of the advantages and disadvantages of cognitive metaphor theory for the analysis of literary texts. The second aim of the collection is to illustrate a range of successful applications of the new cognitive models to literary texts. And, the third aim of the study is to provide an assessment of cognitive metaphor theory from a literary point of view. In this innovative collection, an international group of scholars come together to discuss literary metaphors and cognitive metaphor theory. The volume's goals are three-fold. The first aim of the book is to present some recent approaches to metaphor which have no immediate connection with cognitive metaphor theory and have developed independently of it. While the cognitive approach has become the leading paradigm in the English speaking world, elsewhere (in Europe) rhetorical, semantic, and logical models have remained in use and continue to be elaborated. These models have so far had little international exposure. Their inclusion in this study is meant to provide a balance to the cognitive paradigm and to open up a possible discussion of the advantages and disadvantages of cognitive metaphor theory for the analysis of literary texts. The second aim of the collection is to illustrate a range of successful applications of the new cognitive models to literary texts. And, the third aim of the study is to provide an assessment of cognitive metaphor theory from a literary point of view.In this innovative collection, an international group of scholars come together to discuss literary metaphors and cognitive metaphor theory. The volume's goals are three-fold. The first aim of the book is to present some recent approaches to metaphor which have no immediate connection with cognitive metaphor theory and have developed independently of it. While the cognitive approach has become the leading paradigm in the English speaking world, elsewhere (in Europe) rhetorical, semantic, and logical models have remained in use and continue to be elaborated. These models have so far had little international exposure. Their inclusion in this study is meant to provide a balance to the cognitive paradigm and to open up a possible discussion of the advantages and disadvantages of cognitive metaphor theory for the analysis of literary texts. The second aim of the collection is to illustrate a range of successful applications of the new cognitive models to literary texts. And, the third aim of the study is to provide an assessment of cognitive metaphor theory from a literary point of view. In this innovative collection, an international group of scholars come together to discuss literary metaphors and cognitive metaphor theory. The volume's goals are three-fold. The first aim of the book is to present some recent approaches to metaphor which have no immediate connection with cognitive metaphor theory and have developed independently of it. While the cognitive approach has become the leading paradigm in the English speaking world, elsewhere (in Europe) rhetorical, semantic, and logical models have remained in use and continue to be elaborated. These models have so far had little international exposure. Their inclusion in this study is meant to provide a balance to the cognitive paradigm and to open up a possible discussion of the advantages and disadvantages of cognitive metaphor theory for the analysis of literary texts. The second aim of the collection is to illustrate a range of successful applications of the new cognitive models to literary texts. And, the third aim of the study is to provide an assessment of cognitive metaphor theory from a literary point of view.
Keywords: metaphor; narrative; genre; satire

“The Shaping Spirit and Rousseau: Literary Cosmology, Cognition and Culture.” - Sinding, Michael (Northrop Frye 100: A Danubian Perspective., 2014)
Frye’s approach to culture integrates bodily, cognitive, semiotic, social, and historical factors. Yet productive dialogue with other approaches is challenging: sympathizers may get stuck “inside” his capacious thinking, while skeptics remain “outside” – today, typically emphasizing contextual factors shaping cultural texts (e.g., ideology). I explore an integrative approach via Frye’s account of the inversion of the axis mundi. Frye’s principle that thought and meaning are structured by metaphor and narrative is central to cognitive science today (Lakoff and Johnson, Turner, Hogan). Studies of cultural and cognitive change and stability (e.g. Greenblatt, Zunshine) can therefore profit from his vision of intertwined imaginative-cultural processes. Frye sees early cultures as rooted in mythologies (canonical narratives addressing “primary concerns”), which mentally crystallize into cosmologies. These world-pictures are organized by spatial metaphors based on the orientation of the human body (e.g. the axis mundi). Cosmologies become frameworks for later literary and theoretical structures. Changes in cosmology, then, affect all of human experience. The most profound change in Western cultural history was the 18th-century inversion of the axis mundi: the locus of value and power shifted from God (above and outside) to humanity (below and within). To develop this account, I examine how cosmological structures inform Rousseau’s revolutionary early Discourse on the Arts and Sciences (Words 239-43), and therein mediate historical change. I identify key spatial metaphors and myths, and assess how they embody and manipulate “image-schemas” such as the vertical scale (up/down) and container (in/out). Analysis indicates that the language of Rousseau's argument reorganizing the traditional cosmology focuses on the inner/ outer contrast more than on an axial above/ below contrast. Causal relations among souls depend primarily on the attachment or detachment of inner substance to outer surfaces: attached soul-substances get pulled apart, weaken, decline, and dissolve; while the detached soul, contained in and oriented to itself, remains solid (integrity) and (if ordinary) attends to words within, or (if extraordinary) rises up strongly and attaches to great things above and beyond.
Keywords: Northrop Frye; Rousseau; literary cosmology; cultural worldview; conceptual metaphor

“The Turn to the Mind, Inside and Out” - Sinding, Michael (2010)
<p class="Bibl_Angaben_rez_Text" style="margin: 0mm 0mm 6.35mm 20mm; border-style: hidden; border-color: rgb(0, 0, 0); float: none; line-height: normal; padding: 0mm; break-after: auto; font-weight: bold; font-family: Arial, sans-serif; font-size: 11pt; vertical-align: baseline; color: rgb(0, 0, 0);"> »Imagining Minds: Cognitive Approaches to Narrative, Embodied Simulation, Metaphor and Complex Tropes.« Vienna, May 21 to 24, 2008.  <p class="Absatz_Haupttext" style="margin: 0mm 0mm 4.23mm; border-style: hidden; border-color: rgb(0, 0, 0); float: none; line-height: normal; padding: 0mm; break-after: auto; font-family: Arial, sans-serif; font-size: 11pt; vertical-align: baseline; color: rgb(0, 0, 0);"> Michael Kimmel and Thomas Eder brought together established experts and younger researchers at the University of Vienna in May 2008 to reflect on and contribute to the »cognitive turn«, a major development in recent cultural theory and criticism. This turn, as the conference program said, grounds literary reception in general human psychology and everyday knowledge without losing sight of the specificity of literary aesthetics. It addresses central topics of literary structure and response in new ways. I will briefly contextualize the conference’s themes, review the papers and comment on them, then discuss them in light of some recent debates in the Journal of Literary Theory.

Toward a Cognitive Sociology of Genres - Sinding, Michael (Cognition, Literature, and History, 2013)
Cognition, Literature, and History models the ways in which cognitive and literary studies may collaborate and thereby mutually advance. It shows how understanding of underlying structures of mind can productively inform literary analysis and historical inquiry, and how formal and historical analysis of distinctive literary works can reciprocally enrich our understanding of those underlying structures. Applying the cognitive neuroscience of categorization, emotion, figurative thinking, narrativity, self-awareness, theory of mind, and wayfinding to the study of literary works and genres from diverse historical periods and cultures, the authors argue that literary experience proceeds from, qualitatively heightens, and selectively informs and even reforms our evolved and embodied capacities for thought and feeling. This volume investigates and locates the complex intersections of cognition, literature, and history in order to advance interdisciplinary discussion and research in poetics, literary history, and cognitive science.
Keywords: genre; conceptual blending; ideology; epistolary novel; Samuel Richardson